Analisis Kesalahan Ejaan Bahasa Indonesia pada Berita di Portal Berita Online Tribun-Timur.com (Tribun Sidrap) - Hatimah, Huznul; Saaifullah, Saifullah; Kasman, Rosmini (Nuances of Indonesian Language, 2023)
The aim of this research is to describe Indonesian spelling errors in news on the online news portal Tribun-Timur.com. This research uses a descriptive qualitative approach. This research focuses on spelling errors, namely the use of letters, writing words, and the use of punctuation marks. The data in the research are words or sentences that contain spelling errors. The data source in this research is news on the online news portal Tribun-Timur.com (Tribun Sidrap) January 2023 edition. The data collection techniques used in this research are reading techniques, note-taking techniques and documentation techniques. The data analysis techniques used in this research are data collection, data reduction, data presentation, and drawing conclusions.From the research results, it was found that there were 1 errors in using capital letters, 9 errors in using italics, 4 errors in writing basic words, 2 errors in writing affix words (prefixes), 4 errors in writing combinations of words, 2 errors in writing combinations of words, 2 errors in writing prepositions. , 3 errors in writing abbreviations and acronyms, 2 errors in writing numbers and numbers, and 12 errors in using commas.